Developments in laser trabeculoplasty. Issue 1 (16th September 2015) - Tsang, Susanna; Cheng, Jason; Lee, Jacky WY
Abstract : Laser trabeculoplasty has an increasing important role in the management of glaucoma as more emphasis is placed on minimally invasive therapies. In recent years, the following laser trabeculoplasty technologies have been introduced: micropulse laser trabeculoplasty, titanium-sapphire laser trabeculoplasty and pattern scanning trabeculoplasty. These lasers help to reduce the intraocular pressure (IOP) and the burden of glaucoma medical therapy. Literature findings regarding the safety and efficacy of these newer forms of laser trabeculoplasty in the treatment of open-angle glaucoma is summarised. These relatively newer procedures appear to have similar efficacy when compared with the former selective laser trabeculoplasty or argon laser trabeculoplasty. In addition, they potentially offer a more favourable safety profile with fewer complications, including postlaser inflammation and IOP spikes. Further large-scale studies are necessary to evaluate the long-term benefits of these newer forms of laser trabeculoplasty. Their initial promising results offer patients with glaucoma additional treatment alternatives.